Simulation-Based Training of the Rapid Evaluation and Management of Acute Stroke (STREAM)—A Prospective Single-Arm Multicenter Trial - Bohmann, Ferdinand O.; Kurka, Natalia; du Mesnil de Rochemont, Richard; Gruber, Katharina; Guenther, Joachim; Rostek, Peter; Rai, Heike; Zickler, Philipp; Ertl, Michael; Berlis, Ansgar; Poli, Sven; Mengel, Annerose; et al. (Frontiers in Neurology, 2019)
Introduction: Acute stroke care delivered by interdisciplinary teams is time-sensitive. Simulation-based team training is a promising tool to improve team performance in medical operations. It has the potential to improve process times, team communication, patient safety and staff satisfaction. We aim to assess whether a multi-level approach consisting of a stringent workflow revision based on peer-to-peer review and 2-3 one-day in situ simulation trainings can improve acute stroke care processing times in high volume neurocenters within a six months. Methods and Analysis: The trial is being carried out in a pre-test-post-test design at 7 tertiary care university hospital neurocenters in Germany. The intervention is directed at the interdisciplinary multiprofessional stroke teams. Before and after the intervention, process times of all direct-to-center stroke patients receiving IV thrombolysis (IVT) and/or endovascular therapy (EVT) will be recorded. The primary outcome measure will be the ‘door-to-needle’ time of all consecutive stroke patients directly admitted to the neurocentrers who receive IVT. The secondary outcome measures will be intervention-related process times of the fraction of patients undergoing EVT and effects on team communication, perceived patient safety and staff satisfaction via a staff questionnaire. Interventions: We are applying a multi-level intervention in cooperation with three ‘STREAM multipliers’ from each center. First step is a central meeting of the multipliers at the sponsor’s institution with the purposes of algorithm review in a peer-to-peer process that is recorded in a protocol and an introduction to the principles of simulation traing and debriefing as well as crew resource management and team communication. Thereafter, the multipliers cooperate with the stroke team trainer from the sponsor’s institution to plan and execute 2-3 one-day simulation courses in situ in the emergency department and CT room of the trial centers whereupon they receive teaching materials to perpetuate the trainings. Clinical trial registration: STREAM is a registered trial at https://clinicaltrials.gov/ct2/show/ NCT03228251